The Effect of Intangible Assets, Firm Size, and Tax Expense on Transfer Pricing in Healthcare Companies Listed on the Indonesia Stock Exchange from 2019 to 2024 - Rina Amelia; Yessica Amelia; Ruslaini Ruslaini (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to investigate the impact of intangible assets, firm size, and tax expense on transfer pricing in healthcare companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2024. The research utilizes the annual financial reports of the companies published by the IDX. A quantitative approach was employed with a purposive sampling technique, which resulted in a sample of 12 companies. To analyze the effect of intangible assets, firm size, and tax expense on transfer pricing, the study used Partial Least Squares-based Structural Equation Modeling (SEM-PLS). The findings indicated that intangible assets and firm size had a negative effect on transfer pricing, suggesting that larger companies and those with higher intangible assets tend to engage less in transfer pricing strategies. On the other hand, tax expenses were found to have no significant impact on transfer pricing. These results provide insights into how certain company characteristics influence transfer pricing practices in the healthcare sector. The study's findings also highlight the need for further research to explore other factors that could affect transfer pricing in different industries or countries. Understanding these dynamics can help policymakers and practitioners develop more effective regulations and strategies for managing transfer pricing in multinational corporations.